2022
DOI: 10.3390/ma15051858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Content and Boronizing Parameters on Growth Kinetics of Boride Layers Obtained on Carbon Steels

Abstract: Boronizing is a thermochemical treatment performed to produce hard and wear-resistant surface layers. In order to control the process and obtain boride layers with the desired properties, it is very important to know how the boronizing parameters and the chemical composition of the treated steel affect the boronizing. The aim of the present study is to investigate the influence of carbon content in carbon steels, boronizing temperature, and boronizing duration on the growth kinetics of boride layers. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have mainly investigated the growth kinetics of steel and its alloys. Andrijana Milinović et al [ 33 ] investigated the growth kinetics of different steels, and the results showed that the frequency factor D 0 and diffusion activation energy Q of elemental boron in C15 steel are 3.17 × 10 −4 m 2 /s and 194.80 kJ/mol, respectively. Figure 3 shows the BL and the whole layer thickness as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mainly investigated the growth kinetics of steel and its alloys. Andrijana Milinović et al [ 33 ] investigated the growth kinetics of different steels, and the results showed that the frequency factor D 0 and diffusion activation energy Q of elemental boron in C15 steel are 3.17 × 10 −4 m 2 /s and 194.80 kJ/mol, respectively. Figure 3 shows the BL and the whole layer thickness as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…This is the typical morphology formed on lowcarbon steels when they are exposed to the boriding process [24,25]. Different researchers have reported that the characteristic saw-tooth boride layer morphology is seen in low-alloy steels, unalloyed low-carbon steels, and pure iron [27,41,42]. The layers' thickness ranged from approximately 30 to 218 µm for the samples exposed to 850 • C for 2 h and the samples exposed to 1000 • C and 6 h, respectively.…”
Section: Boriding Treatmentmentioning
confidence: 96%
“…The relationship between the thickness of the boronizing layer and the boronizing temperature is shown in Fig 2 . It is shown that the boronizing layer thickness increased with the increase in boronizing temperature. With the extension of boronizing time, the boronizing layer thickness is nonlinear with the increase of the boronizing temperature [8]. Boriding is a typical reaction-diffusion process.…”
Section: Growth Kinetics Of Boronizing Layermentioning
confidence: 99%